Biology and grading of pleomorphic xanthoastrocytoma—what have we learned about it?. (4th August 2020) - Vaubel, Rachael; Zschernack, Valentina; Tran, Quynh T.; Jenkins, Sarah; Caron, Alissa; Milosevic, Dragana; Smadbeck, James; Vasmatzis, George; Kandels, Daniela; Gnekow, Astrid; Kramm, Christof; Jenkins, Robert; et al.
Abstract: Pleomorphic xanthoastrocytoma (PXA) is a rare astrocytoma predominantly affecting children and young adults. We performed comprehensive genomic characterization on a cohort of 67 patients with histologically defined PXA (n = 53, 79%) or anaplastic PXA (A‐PXA, n = 14, 21%), including copy number analysis (ThermoFisher Oncoscan, n = 67), methylation profiling (Illumina EPIC array, n = 43) and targeted next generation sequencing (n = 32). The most frequent alterations were CDKN2A/B deletion (n = 63; 94%) and BRAF p.V600E (n = 51, 76.1%). In 7 BRAF p.V600 wild‐type cases, alternative driver alterations were identified involving BRAF, RAF1 and NF1 . Downstream phosphorylation of ERK kinase was uniformly present. Additional pathogenic alterations were rare, with TERT, ATRX and TP53 mutations identified in a small number of tumors, predominantly A‐PXA. Methylation‐based classification of 46 cases utilizing a comprehensive reference tumor allowed assignment to the PXA methylation class in 40 cases. A minority grouped with the methylation classes of ganglioglioma or pilocytic astrocytoma (n = 2), anaplastic pilocytic astrocytoma (n = 2) or control tissues (n = 2). In 9 cases, tissue was available from matched primary and recurrent tumors, including 8 with anaplastic transformation. At recurrence, two tumors acquired TERT promoter mutations and the majority demonstrated additional non‐recurrent copy number alterations. Methylation class was preserved at recurrence. For 62 patients (92.5%), clinical follow‐up data were available (median follow‐up, 5.4 years). Overall survival was significantly different between PXA and A‐PXA (5‐year OS 80.8% vs. 47.6%; P  = 0.0009) but not progression‐free survival (5‐year PFS 59.9% vs. 39.8%; P  = 0.05). WHO grade remained a strong predictor of overall survival when limited to 38 cases defined as PXA by methylation‐based classification. Our data confirm the importance of WHO grading in histologically and epigenetically defined PXA. Methylation‐based classification may be helpful in cases with ambiguous morphology, but is largely confirmatory in PXA with well‐defined morphology.